Visual exploration when surrounded by affordances: Frequency of head movements is predictive of response speed - McGuckian, T.; Cole, M.; Chalkley, D.; Jordet, G.; Pepping, G.-J. (Ecological Psychology, 2019)
Little is known about the actions supporting exploration and their relation to subsequent actions in situations when participants are surrounded by opportunities for action. Here, the movements that support visual exploration were related to performance in an enveloping football (soccer) passing task. Head movements of experienced football players were quantified with inertial measurement units. In a simulated football scenario, participants completed a receiving-passing task that required them to indicate pass direction to one of four surrounding targets, as quickly as they could after they gained simulated ball possession. The frequency of head movements before and after gaining ball possession and the pass response times were recorded. We controlled exploration time - the time before gaining simulated ball possession - to be 1, 2, or 3 seconds. Exploration time significantly influenced the frequency of head movements, and a higher frequency of head turns before gaining ball possession resulted in faster pass responses. Exploratory action influenced subsequent performatory action. That is, higher frequencies of head movements resulted in faster decisions. Implications for research and practice are discussed.